Applied research on forest plantation trial of olea europaea in Bushehr Province - Javad Rashidi; Hossein Sardabi (تحقیقات جنگل و صنوبر ایران, 2014)
The aim of the study was to develop forest plantation at appropriate sites of Bushehr province for environmental purposes and to extend olive plantation on marginal lands for economical purposes and to improve local people livelihood. For this reason 12 varieties of Olea europaea including Arbakin, Zard zeitoon, Roghani Roodbari, Mari, Mishen, Lichio, Lemski, Shengeh, Sabz Zeitoon, Sevilana, Beledi and Manzalina were planted on a site located in Chahvak Agricultural Experimental Station in 1997 under statistical design of Randomized Complete Blocks with three replicates and 7 x 8 m. spacing and 10 seedlings per plot. The variance analysis and Duncan test were applied to analyze the data. The data analysis showed that there was significant difference (p